76.2k views
4 votes
3(x - 2) + 4 = 2x -1

2 Answers

4 votes

Answer:

- 1

Explanation:

Step 1:

3 ( x - 2 ) + 4 = 2x - 1 Equation

Step 2:

3x - 6 + 4 = 2x - 1 Multiply

Step 3:

3x - 2 = 2x - 1 Combine Like Terms

Step 4:

3x = 2x - 1 + 2 Add 2 on both sides

Step 5:

3x = 2x - 1 Combine Like Terms

Step 6:

x = - 1 Subract 2x on both sides

Answer:

x = - 1

Hope This Helps :)

User Mikewilliamson
by
4.5k points
4 votes


\text {Hi! Let's Solve this Equation!}


\text {The First Step is to Simplify the Equation:}


\text {3 becomes 3x. 3*-2=-6 so that becomes -6.}


\text {Add: -6+4=-2}


\text {Your new Problem should be: 3x+-6+4=2x-1}


\text {The Next Step is to Subtract 2x:}


\text {3x-2-2x=2x-1-2x}\\\text {x-2=-1}


\text {The Final Step is to Add 2:}


\text {x-2+2=-1+2}


\text {Your Answer should be:}


\fbox {x=1}


\text {Best of Luck!}


\text {-LimitedX}

User JamesM
by
4.8k points